2021
DOI: 10.1111/all.14331
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects in allergen immunotherapy—An EAACI Task Force Position Paper

Abstract: The placebo (Latin “I will please”) effect commonly occurs in clinical trials. The psychological and physiological factors associated with patients’ expectations about a treatment's positive and negative effects have yet to be well characterized, although a functional prefrontal cortex and intense bidirectional communication between the central nervous system and the immune system appear to be prerequisites for a placebo effect. The use of placebo raises certain ethical issues, especially if patients in a plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 129 publications
4
56
0
1
Order By: Relevance
“… 47 The placebo effect in DBPC trials using AECs ranged from +11% to +0,5% after 6 months using the TNSS (−7% after 4 months in 1 trial), and −4% to −17% after 6 months using the Total Ocular Symptom Score in house dust mite (HDM) allergic patients with sublingual immunotherapy (SLIT), and was −18.5% in grass SLIT (Rhinoconjunctivitis Total Symptom Score after 4 months) and −18.8% in birch subcutaneous immunotherapy (SCIT) (TSS after 10 weeks). 48 The efficacy of the symbiotic product in our study exceeded these previously reported effects of placebo groups in AEC trials with a reduction in the median TNSS of 50% and median TSS of 80%. So, even without being able to control for placebo effects in this study, we are confident that the symbiotic product shows clinically relevant improvement for patients with allergic rhinitis.…”
Section: Discussionsupporting
confidence: 52%
“… 47 The placebo effect in DBPC trials using AECs ranged from +11% to +0,5% after 6 months using the TNSS (−7% after 4 months in 1 trial), and −4% to −17% after 6 months using the Total Ocular Symptom Score in house dust mite (HDM) allergic patients with sublingual immunotherapy (SLIT), and was −18.5% in grass SLIT (Rhinoconjunctivitis Total Symptom Score after 4 months) and −18.8% in birch subcutaneous immunotherapy (SCIT) (TSS after 10 weeks). 48 The efficacy of the symbiotic product in our study exceeded these previously reported effects of placebo groups in AEC trials with a reduction in the median TNSS of 50% and median TSS of 80%. So, even without being able to control for placebo effects in this study, we are confident that the symbiotic product shows clinically relevant improvement for patients with allergic rhinitis.…”
Section: Discussionsupporting
confidence: 52%
“…348,349 Recently, the EAACI has published a Position Paper reporting the impact of the placebo effect in AIT from different methodological perspectives and outlining possible strategies to minimize this bias in clinical trials. 350 Taken together, further emphasis should be put on international collaborations of clinical experts, methodologists and regulatory authorities to optimize methodological standards for AIT clinical development programs aimed to increase the level of evidence of AIT as the only disease-modifying therapy available. 334,337,351…”
Section: B I Omark Er S Of the Epithelial Barriermentioning
confidence: 99%
“…One researcher (IK) use the terms "placebo/nocebo response" and "placebo/nocebo effect" in the opposite way [5]. In a recent position paper from the European Academy of Allergy and Clinical Immunology, the term "placebo effect" was defined as "the psychological and physiological benefits of seeking advice and receiving treatment for a medical problem, independently of the prescribed treatment's pharmacological effects per se" [6]. Historical and traditional reasons may explain the differences.…”
Section: The Effect -Response Controversymentioning
confidence: 99%